2017
DOI: 10.1016/j.autneu.2017.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Central TrkB blockade attenuates ICV angiotensin II-hypertension and sympathetic nerve activity in male Sprague-Dawley rats

Abstract: Increased sympathetic nerve activity and the activation of the central renin-angiotensin system are commonly associated with cardiovascular disease states such as hypertension and heart failure, yet the precise mechanisms contributing to the long-term maintenance of this sympatho-excitation are incompletely understood. Due to the established physiological role of neurotrophins contributing towards neuroplasticity and neuronal excitability along with recent evidence linking the renin-angiotensin system and brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 67 publications
1
13
0
Order By: Relevance
“…As examples, ANG II has been shown to upregulate brain-derived neurotrophic factor (BDNF) and its receptor TrkB in catecholaminergic cells, leading to p38MAPK-dependent reduction in voltagegated K ϩ current (64). TrkB blockade decreases the pressor and sympathoexcitatory effects of centrally administered ANG II, suggesting that the BDNF/TrkB pathway is required to mediate ANG II-dependent responses (63). Interestingly, central infusion of an AT 1 R blocker, losartan, or an ACE inhibitor, lisinopril, as well as ganglionic blockade attenuates central BDNF-induced blood pressure elevation (924), further suggesting a feed-forward relationship in brain between the BDNF/TrKB pathway and the RAS.…”
Section: Sympathoexcitatory Actionmentioning
confidence: 99%
“…As examples, ANG II has been shown to upregulate brain-derived neurotrophic factor (BDNF) and its receptor TrkB in catecholaminergic cells, leading to p38MAPK-dependent reduction in voltagegated K ϩ current (64). TrkB blockade decreases the pressor and sympathoexcitatory effects of centrally administered ANG II, suggesting that the BDNF/TrkB pathway is required to mediate ANG II-dependent responses (63). Interestingly, central infusion of an AT 1 R blocker, losartan, or an ACE inhibitor, lisinopril, as well as ganglionic blockade attenuates central BDNF-induced blood pressure elevation (924), further suggesting a feed-forward relationship in brain between the BDNF/TrKB pathway and the RAS.…”
Section: Sympathoexcitatory Actionmentioning
confidence: 99%
“…BDNF influences endothelial function [ 163 ], monocyte activation [ 154 ], and thrombus dimension and stability [ 164 ]. It takes part to cardiovascular development [ 165 ] but also to the onset of cardiovascular alterations and disease [ 166 ], including hypertension [ 167 , 168 ], atherosclerosis [ 169 , 170 ] and thrombosis. Reduced BDNF plasma levels has been found in metabolic syndrome [ 170 ], ACS [ 171 , 172 ], and type 2 diabetes [ 173 ], suggesting that alterations in its circulating levels may be associated to pathological conditions.…”
Section: Adipokinesmentioning
confidence: 99%
“…The role of NT-4 and related pathways in CVD are not well characterized; however, binding the same receptor of BDNF (Tropomyosin receptor kinase B-TrkB), it might have similar functions of BDNF in controlling blood pressure [ 168 ].…”
Section: Adipokinesmentioning
confidence: 99%
“…Goel et al showed the evidence that chronic neuroinflammation and memory impairment in hypertension—associated with increased apoptotic cell death and with amyloid beta deposition—can be prevented with candesartan treatment, suggesting partly to be explained by an increase of BDNF/CREB (cAMP response element binding protein) expression (Goel et al 2017 ). Furthermore, the connection between RAS and TrkB signaling is proven in vitro (Becker et al 2015 ) and in vivo as well, as Becker et al demonstrated the mediator role of BDNF-TrkB signaling on Ang II-induced mean blood pressure and renal sympathetic nerve activity elevation in male rats (Becker et al 2017 ). Thus probably RAS blockers restore BDNF through TrkB signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…As TrkB is a mediator of the long-term blood pressure and sympathetic nerve activity responses to central angiotensin II activity (Becker et al 2017 ), NT-4—binding the same TrkB-receptor—might have similar functions, even if the role of NT4/TrkB signaling in sympathetic control of blood pressure is still even less precisely understood than BDNF/TrkB signaling.…”
Section: Introductionmentioning
confidence: 99%